Successful weight maintainers among young adults—A ten-year prospective population study. (April 2018) - Kärkkäinen, Ulla; Mustelin, Linda; Raevuori, Anu; Kaprio, Jaakko; Keski-Rahkonen, Anna
Abstract: Objectives: To assess factors associated with successful weight maintenance over ten years in a prospective general population sample of young adults. Material and methods: Our study comprised 2452 women and 2227 men born in 1975–1979 (mean age at baseline 24 years, attrition 27.1%). Weight maintenance was defined as weight maintained within ±5% of baseline body mass index (BMI). We examined the role of various sociodemographic and lifestyle factors in successful weight maintenance. Results: Relatively few young adults were able to maintain their weight over ten years (28.6% of women vs. 23.0% of men); net weight loss was uncommon (7.5% and 3.8%). Most participants gained weight (mean annual weight gain was 0.9 kg in women and 1.0 kg in men). Among women, exercise was associated with successful weight maintenance, but having two or more children, frequent use of sweet drinks, irregular eating, history of dieting (intentional weight loss) and low life satisfaction were associated with weight gain. Among men, higher baseline BMI and higher education were associated with successful weight maintenance, whereas irregular eating, history of dieting and smoking were associated with weight gain. Conclusions: Only about a quarter of young adults were able to resist weight gain. Regular eating and having no history of dieting were associated with successful weight maintenance in young women and men. Highlights: Our study documents an important period during young adulthood when weight maintenance is challenging for the majority. Preventing initial weight gain is an essential population-level target, yet those factors remain poorly understood. This study quantifies factors associated with long-term weight maintenance in the general population among young adults. Regular eating and having no history of dieting were associated with weight maintenance in young women and men. Other factors associated with long-term successful weight maintenance were sex-specific.